PELATIHAN FOTO PRODUK UNTUK PENGUATAN PEMASARAN UMKM DI KECAMATAN MERAKURAK KABUPATEN TUBAN PADA MASA PANDEMI COVID-19 - Dian Rustyawati; Nur Laili Dinahafni; Nadiya Qurota Akyun (Al Hikmah: Jurnal Studi Keislaman, 2021)
Abstract, Higher education is a place of learning for students and has a big role in theformation of competitive character and human resources in society. These studentswill grow into educated, creative, innovative, and empowered human beings inproviding positive changes to society. Therefore, universities can increase their role inbringing about change in society, including in the fields of education, culture, social,economics, and various other fields. Through Product Photo Training forStrengthening MSMEs in Merakurak District, Tuban Regency during the Covid-19Pandemic, IAINU Tuban hopes to be able to contribute knowledge so that MSMEs inMerakurak District can improve their business marketing and be able to surviveduring the pandemic. Increasing the ability in product photos for MSMEs is expectedto be able to support them in increasing business marketing, one of which is bycreating an online catalog. It is hoped that after participating in this training, MSMEactivists can optimize the facilities they have for business development, carry outmarketing innovations, and in the end can replicate these skills to be taught to otherMSME activists. Through this training, many good hopes were raised. The moreMSMEs that are able to make good product photos, the greater the opportunity toincrease entrepreneurship and bring changes in people's lives for the better.Improving the economy, solving social problems, and building empoweredcommunities.Keywords: photo, product, marketing, entrepreneurship, umkm